Legacies and Lifespans in Contemporary Women’s Writing
X, 218 p.
Keywords: This book examines the connections and conversations between women writers from the twentieth century and the twenty-first century. The essays consider the ways in which twenty-first-century women writers look back and respond to their predecessors within the field of contemporary women’s writing. The book looks back to the foundations of contemporary women’s writing and also considers how this category may be defined in future decades. We ask how writers and readers have interpreted ‘the contemporary’, a moving target and an often-contentious term, especially in light of feminist theory and criticism of the late twentieth century. Writing about the relationships between women’s writings is an always-vital, ongoing political project with a rich history. These essays argue that establishing and defining the contemporary is, for women writers, another ongoing political project to which this collection of essays aims, in part, to contribute.